Dynamics of Cereal Crops in Chitwan: Trends and Issues - Chalise, Samyak Raj; Marahatta, Santosh (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2025)
This research article studies the present condition of cereal crops production in Chitwan and identifies the issues in cereal crop production and yielding in Chitwan. Chitwan, a district in the central part of Nepal, has a value in agricultural production to the whole country. Chitwan faces many ups and downs in the cereal crops production and yielding time and again. These up and down have an impact to the total life of Nepal. This study uses the existing archival data and follows the analysis and interpretation approach to reach to the conclusion that land use, productivity, environment and wild-life, and technological and socio-economic constraints are the issues affecting cereal crop production and yielding in Chitwan. Further, it identifies that lack of farming efficiency; absence of promoting cereals holds potential for enhancing food security, environmental threats and economic instability are the critical issues of cereal crop production and yielding in Chitwan today. Key factors influencing the adoption of organic vegetable farming in the area include farm size, farmers' participation in organic farming training, and the compatibility of organic practices with local conditions. Farmer perception, motivation, and involvement in extension activities are critical determinants of farming adoption. Chitwan's agricultural capacity, coupled with its climate and forest resources, makes it a promising area for cultivating high-yielding varieties of crops such as rice, wheat and maize. This research is meaningful in identifying present condition and major challenges of cereal crops production and yielding in Chitwan and to recommend some ways to cope with those challenges.